Pulmonary haemorrhage as the earliest sign of severe leptospirosis in hamster model challenged with Leptospira interrogans strain HP358 - Philip, Noraini; Priya, Sivan Padma; Jumah Badawi, Ahmad Hussein; Mohd Izhar, Mohd Hafidz; Mohtarrudin, Norhafizah; Tengku Ibrahim, Tengku Azmi; Sekawi, Zamberi; Neela, Vasantha Kumari (Public Library of Science, 2022)
Background Severe leptospirosis is challenging as it could evolve rapidly and potentially fatal if appropri-ate management is not performed. An understanding of the progression and pathophysiology of Leptospira infection is important to determine the early changes that could be potentially used to predict the severe occurrence of leptospirosis. This study aimed to understand the kinetics pathogenesis of Leptospira interrogans strain HP358 in the hamster model and iden-tify the early parameters that could be used as biomarkers to predict severe leptospirosis. Methodology/Principal findings Male Syrian hamsters were infected with Leptospira interrogans strain HP358 and eutha-nized after 24 hours, 3, 4, 5, 6 and 7 days post-infection. Blood, lungs, liver and kidneys were collected for leptospiral detection, haematology, serum biochemistry and differential expression of pro-and anti-inflammatory markers. Macroscopic and microscopic organ damages were investigated. Leptospira interrogans strain HP358 was highly pathogenic and killed hamsters within 6–7 days post-infection. Pulmonary haemorrhage and blood ves-sel congestion in organs were noticed as the earliest pathological changes. The damages in organs and changes in biochemistry value were preceded by changes in haematology and immune gene expression. Conclusion/Significance This study deciphered haemorrhage as the earliest manifestation of severe leptospirosis and high levels of IL-1β, CXCL10/IP-10, CCL3/MIP-α, neutrophils and low levels of lymphocytes and platelets serve as a cumulative panel of biomarkers in severe leptospirosis.